Effect of Time Management Training on Work-Family Conflict among Hospital Nurses - P Rasooli (MSc.); HR Khankeh (Ph.D); M Falahi Khoshknab (Ph.D); M Rahgozar (Ph.D) (Tehran University of Medical Sciences, 2009)
Background & Aim: The present research attempted to investigate the effect of time management training on work-life conflict among two hospitals' nurses. Methods & Materials: In this randomized trial, we recruited all nurses of two public hospitals (n=106) in Hamadan and Tehran according to the inclusion criteria. We used balanced (permuted) block randomization for assigning the study sample into control (n=53) and intervention (n=47) groups. Six individuals did not participate in the study. Data were collected using two instruments: 1) work-family conflict scale; and 2) time management behaviors scale. For content validity, ten experts in the field of the study commented on the items. The reliability coefficients (Cronbach's alpha) for these scales were 0.86 and 0.75, respectively. All participants completed the questionnaires at baseline. The time management skills were taught in the intervention group for eight hours. One month later, all participants in two groups completed the questionnaires again. Results: Considering the baseline characteristics, the groups were homogenous. Independent sample t-test indicated no significant differences between the two groups in all dimensions before the intervention (P>0.05). There was significant difference between two groups in the work-family conflict after the intervention (P<0.001). Also, the paired t-test showed significant difference in work-family conflict before and after the intervention in the intervention group (P<0.001). Conclusion: According to our findings in the present research, time management training intervention had positive effect on work-family conflict among hospital nurses.   Key words: conflict, nurses, time management, work